Mental Pain in People With Bipolar Disorder Hospitalized in a Psychiatric Hospital in Tehran, Iran - Samira Alvandi; Marjan Mardani-Hamooleh; Fariba Ghasemi; Nazanin Esmaeeli; Shima Haghani (Iran University of Medical Sciences, 2022)
Background & Aims: Mental disorders are associated with a complex self-centered experience of negative emotions such as despair and lack of mental pain. This study aims to determine the mental pain of people with bipolar disorder (BD) hospitalized in a psychiatric hospital in Tehran, Iran. Materials & Methods: This is a cross-sectional study. Participants were 153 patients with BD admitted to Iran Psychiatric hospital, who were selected by continuous sampling. Data collection tools were a demographic form and Orbach Mikulincer Mental Pain (OMMP) Scale. Data were analyzed in SPSS software, version 16 software using descriptive and inferential statistics. Results: The mean score of OMMP scale in patients was 109.56±36.93. The variables of suicide attempt (P<0.001), economic status (P=0.002), and employment status (P=0.02) status had a significant relation with the mental pain of patients.  Conclusion: The mental pain of hospitalized patients with BD in Tehran is at a moderate level. Patients with poor financial status, unemployed patients, and those with a history of suicide attempt have higher mental pain.